2015
DOI: 10.1104/pp.15.00315
|View full text |Cite
|
Sign up to set email alerts
|

The Gymnosperm Cytochrome P450 CYP750B1 Catalyzes Stereospecific Monoterpene Hydroxylation of (+)-Sabinene in Thujone Biosynthesis in Western Redcedar

Abstract: Western redcedar (WRC; Thuja plicata) produces high amounts of oxygenated thujone monoterpenoids associated with resistance against herbivore feeding, particularly ungulate browsing. Thujones and other monoterpenoids accumulate in glandular structures in the foliage of WRC. Thujones are produced from (+)-sabinene by sabinol and sabinone. Using metabolite analysis, enzyme assays with WRC tissue extracts, cloning, and functional characterization of cytochrome P450 monooxygenases, we established that transsabin-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…In the CYP71 clan, 8 CYP76AA and 18 CYP750 gymnosperm-specific members were identified among the 118 full-length CYP450s. Previous research revealed that the gymnosperms CYP76AA25 and CYP750B1 can catalyze the hydroxylation of sabinene to trans-sabin-3-ol from Thuja plicata (Bohlmann et al, 2015 ). The CYP85 clan, which includes many gymnosperm CYP450s, is involved in the biosynthesis of plant metabolites (Hamberger and Bohlmann, 2006 ; Zerbe et al, 2013 ): the CYP720B is a conifer-specific subfamily with four members in T. chinensis , and the CYP720B4 has been characterized in the biosynthesis of dehydroabietic acid, an ingredient related to the insect resistance of Picea sitchensis (Hamberger et al, 2011 ); the CYP716B is a gymnosperm-specific subfamily, with three members found in T. chinensis , and the sole functionally determined CYP716B gene is a taxoid 9α-hydroxylase in Ginkgo biloba (Zhang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the CYP71 clan, 8 CYP76AA and 18 CYP750 gymnosperm-specific members were identified among the 118 full-length CYP450s. Previous research revealed that the gymnosperms CYP76AA25 and CYP750B1 can catalyze the hydroxylation of sabinene to trans-sabin-3-ol from Thuja plicata (Bohlmann et al, 2015 ). The CYP85 clan, which includes many gymnosperm CYP450s, is involved in the biosynthesis of plant metabolites (Hamberger and Bohlmann, 2006 ; Zerbe et al, 2013 ): the CYP720B is a conifer-specific subfamily with four members in T. chinensis , and the CYP720B4 has been characterized in the biosynthesis of dehydroabietic acid, an ingredient related to the insect resistance of Picea sitchensis (Hamberger et al, 2011 ); the CYP716B is a gymnosperm-specific subfamily, with three members found in T. chinensis , and the sole functionally determined CYP716B gene is a taxoid 9α-hydroxylase in Ginkgo biloba (Zhang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most closely related and functionally defined P450s are L. japonicus LjCYP736A2 (cyanogenic glucoside metabolism; Takos et al, 2011) and S. aucuparia SoCYP736A107 (noraucuparin formation in biphenyl phytoalexin biosynthesis; Sircar et al, 2015). The CYP750B1 sabinene hydroxylase of the gymnosperm Thuja plicata appears to be the most closely related P450, with a known function in terpenoid oxidation (Gesell et al, 2015). Individually scaled TIC Figure S4).…”
Section: Phylogenetic Relationships For Sacyp736a167mentioning
confidence: 99%
“…The next biosynthetic step leads from sabinene to either (? )-trans-sabinol in the case of gymnosperm T. plicata (Gesell et al 2015) or (-) cis-sabinol in the angiosperm S. officinalis (Karp and Croteau 1982). Gesell et al (2015) identified CYP750B1 and CYP76AA25 as the enzymes catalyzing the hydroxylation of (?…”
mentioning
confidence: 99%
“…)-sabinene to trans-sabin-3-ol. The role of the first enzyme is essential and it seems to be strongly substrate specific, while the CYP76AA25 has a broader substrate spectrum and its transcript profiles were not well correlated with thujone accumulation (Gesell et al 2015). Earlier, Karp and Croteau (1982) suggested (-)-cis-sabinol to be the intermediary of the same pathway in sage; however, it is not known if the synthesis in Artemisia and other species is going on through trans-or cissabinol.…”
mentioning
confidence: 99%